Juridical Analysis Of Law Enforcement Against Criminal Offenders Misusing Subsidized Fuel To Creating The Principle Of Justice (Research Study In Bintan Police Jurisdiction) - Micha Pratama Dewa Dharma; Ramon Nofrial; Erniyanti Erniyanti; Soerya Respationo (Badan Penerbit STIEPARI Press, 2023)
The purpose of the study is to determine legal arrangements in terms of enforcement against perpetrators of subsidized fuel abuse in the Bintan Police Area, to determine the implementation of law enforcement against perpetrators of subsidized fuel abuse in the Bintan Police Area, to find out obstacles and law enforcement solutions against perpetrators criminal misuse of subsidized fuel in the Bintan Police Station area. This thesis research method is normative juridical (legal research) through literature study with an empirical juridical approach (sociological juridical) through field studies aimed at obtaining legal knowledge empirically. The results showed that enforcement legal arrangements against perpetrators of subsidized fuel abuse are strictly enforced to ensure integrity and fairness in the distribution of subsidized energy resources to the people. The government, through various regulations and laws, has imposed significant sanctions on individuals or entities that misuse, divert, or resell subsidized fuel for commercial purposes. Law enforcement by the police against perpetrators of subsidized fuel abuse in Indonesia still requires optimization, although efforts have been made through various operations and raids, there are still reports and evidence showing that criminal acts of subsidized fuel abuse continue to occur in various regions. Obstacles such as lack of resources, coordination between agencies, and obstacles in investigation and prosecution make the law enforcement process not run as optimally as expected. This certainly challenges the integrity of social justice promoted by the government in the fuel subsidy program for people in need. In the implementation of law enforcement against perpetrators of criminal acts of misuse of subsidized fuel, the police are faced with several obstacle factors. First, limited human resources and equipment make law enforcement difficult to conduct thoroughly. Second, lack of inter-agency coordination often slows down investigations and prosecutions. Third, there are indications that the involvement of certain parties who have economic interests can hamper the law enforcement process. Solutions that can be proposed include increasing human resource capacity through training and education, improving infrastructure and supporting equipment, and strengthening inter-agency coordination mechanisms. In addition, transparency and accountability in the law enforcement process must be improved, as well as prioritizing a preventive approach through socialization to the public about the negative impacts of subsidized fuel abuse. It is recommended that the government to strengthen legal policies against perpetrators of criminal acts of misuse of subsidized fuel in order to provide a deterrent effect to perpetrators. The police are advised to improve law enforcement performance against perpetrators of criminal acts of misuse of subsidized fuel that harm the community and the state. The public is advised to participate in assisting the police in law enforcement against perpetrators of the criminal act of misusing subsidized fuel.